The Northern Dimension as a Promising Model of Interaction between the European Union and Great Powers in Times of Aggravation of Disintegration Processes in the European Space - D. A. Lanko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The article discusses the Northern Dimension — the four-lateral policy of the Russian Federation, the European Union, Norway and Iceland — in two instances. On one hand, the Northern Dimension has established itself as an eﬀective instrument of meeting specifc challenges of the northern part of the European continent. On other hand, the article discusses the Northern Dimension as a model of relationship between the EU and its potent neighbours, comparable with Russia in terms of their military power, size of the economy and the scale of political ambitions. The United Kingdom, which is fnishing its exit from the European Union, and which is starting building a new system of relationship with it, has recently emerged as such potent neighbour of the European Union. The article presents the results of analysis based on a dialogue between major theories of European integration: namely neo-functionalism and liberal intergovernmentalism. Combining the two theories allows analysing the roles of individual EU member states — the article focuses on Finland in that context — and of European supranational institutions in the formation of the Norther Dimension; among supranational institutions, the article focuses on the European Commission. The article concludes that Ireland can play a crucial role in the building of future relationship between the European Union and the United Kingdom. The Irish role is comparable with the role that Finland has played in the building of the relationship between the EU and Russia and in developing of the Northern Dimension into an eﬀective and promising model of relationship between the integration union and its great power neighbours.